2020
DOI: 10.1155/2020/8075924
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Conventional Keratometry and Total Keratometry in Normal Eyes

Abstract: Purpose. The relationship between conventional keratometry and total keratometry has not been fully investigated. This study was aimed at conventional keratometry measured with the automated keratometer and total keratometry with the corneal tomographer in ophthalmologically normal subjects. Methods. We enrolled fifty eyes of 50 consecutive subjects (mean age±standard deviation, 34.9±8.0 years) who have no ophthalmologic diseases, other than refractive errors, with no history of ocular surgery. Conventional ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Refractive predictability was excellent in our study, with a mean postoperative residual SE of −0.17 D at 12 months and 95% of the eyes being within ±0.5 D of the target value. This suggests that advanced, swept source-based optical biometry 26 and modern IOL calculation formulae, such as the Barrett TK formula 27 , 28 used in the present study, may help cataract refractive surgeons to improve their chances of achieving postoperative targets closer to emmetropia in the majority of their cases.…”
Section: Discussionmentioning
confidence: 92%
“…Refractive predictability was excellent in our study, with a mean postoperative residual SE of −0.17 D at 12 months and 95% of the eyes being within ±0.5 D of the target value. This suggests that advanced, swept source-based optical biometry 26 and modern IOL calculation formulae, such as the Barrett TK formula 27 , 28 used in the present study, may help cataract refractive surgeons to improve their chances of achieving postoperative targets closer to emmetropia in the majority of their cases.…”
Section: Discussionmentioning
confidence: 92%
“…There were no eyes with >0.5D astigmatism difference between the TK and ssOCT-K groups similar to that reported earlier. 23 Analysis of the vectors, as shown in Tables 5 and 6, showed great agreement between the astigmatism vector mean of TK and ss-OCT (difference of 0.09 ± 0.43), OCLR-K (difference of 0.06 ± 0.43), and TCP (difference of 0.06 ± 0.44). The comparison between TK and SimK (difference of 0.31 ± 0.73) showed poorer agreement though not statistically significant.…”
Section: Discussionmentioning
confidence: 74%
“…Even with continuously advanced IOL power calculation formulas, cataract surgery on highly myopic eyes often results in unexpected refractive outcomes [ 12 ]. Recent improvements in TK biometry have demonstrated benefits in IOL calculation [ 16 , 17 , 27 29 ], but few studies have demonstrated its potential in highly myopic eyes, especially for those without prior refractive surgeries [ 13 ]. In this study, we demonstrated that highly myopic eyes with thinner CCTs tend to have larger differences between TK and K methods, while the XGBoost enhancement calculator and RBF 3.0 formula, with either TK or K method, seemed to be the most promising options for IOL power calculation for this special population.…”
Section: Discussionmentioning
confidence: 99%
“…Accuracies of other new formulas such as Cooke K6 formula, and Emmetropia Verifying Optical (EVO 2.0) formulas, remained unknown in highly myopic eyes. Rare previous studies have compared the performance of IOL calculation formulas when applying the new TK over standard keratometry (K) values in normal AL eyes [ 15 , 16 ], or in all AL ranges [ 13 , 17 ], but few in long AL eyes.…”
Section: Introductionmentioning
confidence: 99%